(untitled) (Journal of Economic Research & Business Administration, 2016)
This article is dedicated to financial globalization. The financial globalization improved the fluency of international markets on credit operations and international banking system, what drove us to growth of international flow of financial institutes and corporation business raise abroad and to fundamental changes in their organization systems. In this article you can find as advantages as disadvantages in countries’ globalization. Pros are: competition growth, huge economy. Cons are:a huge economical between different countries , market’s deformation, it’s also a Kazakhstan’s market review here. Following the respond about competition capacity by years 2013-2014 our Republic takes the place №103 of 148 countries. The worst places are connected to «banks stabilization»(№100); «financial points of markets»(№101). By the way , comparing the previous article our country came higher from the place №115 , what means that we increase our economy. Work is also consist the ways of involving countries and the financial growth.